Uneven Urbanisation: Connecting Flows of Water to Flows of Labour and Capital Through Jakarta's Flood Infrastructure. Issue 5 (21st May 2018) - Batubara, Bosman; Kooy, Michelle; Zwarteveen, Margreet
Abstract: This article analyses processes of uneven urbanisation by looking at flood infrastructure. Combining the conceptual frameworks of uneven development with the political ecology of urbanisation, we use flood infrastructure as a methodological device to trace the processes through which unevenness occurs within, but also far beyond, the city of Jakarta, Indonesia. We do this to show how the development of flood infrastructure in Jakarta is shaped by the logic of capitalism through mutually implicated tendencies of socionatural differentiation and equalisation. These processes render waters, resources and labour as similar across places and times to produce different spaces for different populations, within and beyond city boundaries. This theorisation reveals how the urban inequalities (re)produced by flood infrastructure are intimately linked to inequalities (re)produced through the urbanisation of the non‐city.